Aedes Aegypti Hatchability and Larval Development Based on Three Different Types of Water - Thia Prameswarie; Indri Ramayanti; Ahmad Ghiffari; Miranti Dwi Hartanti; Dientyah Nur Anggina; Rista Silvana; Ismail Ismail (Majalah Kesehatan Indonesia, 2023)
Clean water reservoirs can become mosquito breeding grounds because water comes from rainwater, water wells, and taps, making them an ideal breeding ground for the Aedes aegypti mosquito vector of the dengue virus. This study aims to determine the hatchability of eggs and the growth of Aedes aegypti in three different types of brooding water in Sako Village, Palembang City. This study is experimental. The sample contains 1200 Aedes aegypti eggs collected from the Health Research and Development Center (Balitbangkes), the Ministry of Health of Indonesia in Baturaja, as well as three types of water collected from the homes of residents suffering from Dengue Hemorrhagic Fever in Sako Village, Sako District, Palembang City. Data was collected through direct observation for 5 days of egg hatching in the third water, which was repeated three times. The study's results were analyzed by the ANOVA, Honest Significant Difference test (BNJ), and R studio software version 4.1.2. The average number of mosquito eggs that hatched in well water was 77.67%, rainwater was 63,335, tap water was 54.67%, and control was 72.33%. There were significant differences in the effects of the three types of air on the larval and pupal stages of Aedes aegypti development. This study shows that Aedes aegypti mosquitos can breed into adults outside of clean water and water that contains soil, such as water wells. Abstrak: Tempat penampungan air bersih dapat menjadi sarang nyamuk, air berasal dapat berasal dari air hujan, sumur air dan ledeng sehingga menyediakan tempat yang baik bagi nyamuk Aedes aegypti vektor virus dengue untuk berkembang biak.  Penelitian ini bertujuan untuk mengetahui daya tetas telur dan perkembangan Aedes aegypti pada tiga jenis air perindukan di Kelurahan Sako Kota Palembang. Penelitian ini merupakan penelitian eksperimental. Sampel terdiri dari 1200 butir telur Aedes aegypti yang diperoleh dari Litbangkes Kemenkes Baturaja dan tiga jenis air yang diambil dari dari rumah warga yang menderita penyakit Demam Berdarah Dengue yang bertempat tinggal dan menetap di Kelurahan Sako, Kecamatan Sako, Kota Palembang. Pengumpulan data diperoleh dengan melakukan pengamatan langsung selama lima hari terhadap penetasan telur pada ketiga air tersebut yang dilakukan sebanyak tiga kali pengulangan. Hasil penelitian di analisis menggunakan ANOVA, uji Beda Nyata Jujur (BNJ) dan software R studio version 4.1.2. Hasil penelitian menunjukkan rata-rata jumlah telur nyamuk yang menetas di air sumur mencapai 77,67%, air hujan 63,335, dan air PDAM 54,67% dan kontrol sebesar 72,33%. Terdapat perbedaan yang siginfikan pengaruh tiga jenis air terhadap perkembangan stadia larva dan pupa Aedes aegypti. Penelitian ini membuktikan bahwa nyamuk Aedes aegypti mampu berkembang biak menjadi dewasa di luar media air bersih dan air yang dasarnya mengandung tanah seperti air sumur.